134k views
1 vote
Solve the system y = -x + 7 and y = 0.5(x - 3)^2

2 Answers

3 votes

Answer:

The solutions are (-1,8) and (5,2).

Explanation:

User Omer Van Kloeten
by
6.9k points
6 votes

Answer:


x=-1;\ y=8\\x=5;\ y=2

Explanation:

You can make both equations equal and solve for the variable x, as you can see below:


-x+7=0.5(x-3)^2

Keep on mind that:


(a-b)^2=a^2-2ab+b^2

Then:


-x+7=0.5(x-3)^2\\-x+7=0.5(x^2-2(x)(3)+3^2)\\-x+7=0.5x^(2)-3x+4.5\\0=0.5x^2-2x-2.5

Apply the quadratic formula:


x=(-b+/-√(b^2-4ac))/(2a)\\\\x=(-(-2)+/-√((-2)^2-4(0.5)(-2.5)))/(2(0.5))\\x=-1\\x=5

Substitute each value into one of the originl equations to find y, then:


y=-(-1)+7=8\\y=-5+7=2

User Darian Moody
by
5.8k points